Effects of E2HSA, a Long-Acting Glucagon Like Peptide-1 Receptor Agonist, on Glycemic Control and Beta Cell Function in Spontaneous Diabetic db/db Mice - Shaocong Hou; Caina Li; Yi Huan; Shuainan Liu; Quan Liu; Sujuan Sun; Qian Jiang; Chunming Jia; Zhufang Shen (Journal of Diabetes Research)
Glucagon like peptide-1 (GLP-1) receptor agonists such as exendin-4 have been widely used but their short half-life limits their therapeutic value. The recombinant protein, E2HSA, is a novel, long-acting GLP-1 receptor agonist generated by the fusion of exendin-4 with human serum albumin. In mouse pancreatic NIT-1 cells, E2HSA activated GLP-1 receptor with similar efficacy as exendin-4. After single-dose administration in ICR mice, E2HSA showed prolonged glucose lowering effects which lasted up to four days and extended inhibition on gastric emptying for at least 72 hours. Chronic E2HSA treatment in db/db mice significantly improved glucose tolerance, reduced elevated nonfasting and fasting plasma glucose levels, and also decreased HbA1c levels. E2HSA also increased insulin secretion and decreased body weight and appetite. Furthermore, immunofluorescence analysis showed that E2HSA increased β-cell area, improved islet morphology, and reduced β-cell apoptosis. In accordance with the promotion of β-cell function and survival, E2HSA upregulated genes such as Irs2, Pdx-1, Nkx6.1, and MafA and downregulated the expression levels of FoxO1 and proapoptotic Bcl-2 family proteins. In conclusion, with prolonged glucose lowering effects and promoting β-cell function and survival, the fusion protein, E2HSA, is a promising new therapeutic for once weekly treatment of type 2 diabetes.